Diagnostic and therapeutic laparoscopy in the management of endometriosis - Swain, Sujata; Jena, Paresh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Endometriosis associated with a variety of symptoms, primarily produces dysmenorrhea and infertility. Three classes of techniques have been used to diagnose women with endometriosis beside the history and the clinical picture: biochemical markers, radiological imaging and laparoscopic examination of peritoneal cavity. Methods: All 52 patients were evaluated clinically, biochemically, and radiologically and laparascopically to find out the abnormalities. Results: Most common complaint in a patient with endometriosis is dysmenorrhea affecting 67.6% population in this study group. 20% patients presented with infertility. Diagnostic laparoscopy of the patients in the study group show ovarian endometrioma in 67.3% population. Stage II endometriosis was seen in maximum number of cases in the study group comprising 46.2% patients. Ovarian cystectomy was the most common therapeutic procedure done in 51.9% of patients, out of which 40.4% cases treated with unilateral cystectomy and rest by bilateral cystectomy. Conclusions: This study concludes that endometriosis predominantly affects the women of reproductive age group and causes dysmenorrhea and infertility in majority of the patients. A laparoscopic finding marks as a standard tool in diagnosis and treatment of endometriosis.